La influencia del biocomercio en la cadena de valor de exportación de la nuez del Brasil entre los años 2012 y 2019 - Mantilla Mantilla, Tahis Alexandra (2022)
The purpose of this research is to analyse the influence of BioTrade on the Brazilian nuts exports value chain between 2012 and 2019. A mixed research methodology were used, in which we made use of different numerical databases, such as SUNAT, Veritrade, Trademap; as well as interviews with different managers of companies, associations and experts/specialists. In the initial part of the investigation, we will talk about the national and international background that allowed us to create the basis for our investigation. In addition, it explains the theoretical bases that allow us to explain our research. Four hypotheses were proposed to be able to analyse the influence of BioTrade in the export value chain of the Brazilian nut. Among the most important results, we can assert that the Brazilian nut is a dried fruit of the native biodiversity and that it already complies with the definition BioTrade. Finally, we will present the results and analysis carried out on the Brazilian nuts exports value chain, as well as BioTrade. These results include figures, tables and descriptions of the relationship of the aforementioned variables. The analysis was carried out together with the responses of the interviewees and with the collection of data, such as total FOB in millions of dollars, quantities exported in tons and prices.